(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
In this paper we present about Kautilya’s Arthasastra. Itdescribes not only the internal Administration but the external behavior of thestate. All the basic principles of inter - state relations are given inArthasastra. He agrees with imperialism and describes the way to win a state.Kautilya deals with foreign policy, so he is popularly known as the greattheorist of interstate relations because of his unique and unprecedentedcontribution.